Antitrypanosomal Properties of Panax ginseng C. A. Meyer: New Possibilities for a Remarkable Traditional Drug. (4th April 2012) - Herrmann, Florian; Sporer, Frank; Tahrani, Ahmad; Wink, Michael
Abstract : African trypanosomiasis is still a major health problem in many sub‐Saharan countries in Africa. We investigated the effects of three preparations of Panax ginseng, Panax notoginseng, isolated ginsenosides, and the polyacetylene panaxynol on Trypanosoma brucei brucei and the human cancer cell line HeLa. Hexane extracts and the pure panaxynol were toxic and at the same time highly selective against T. b. brucei, whereas methanol extracts and 12 isolated ginsenosides were significantly less toxic and showed only weak selectivity. Panaxynol was cytotoxic against T. b. brucei at the concentration of 0.01 µg/mL with a selectivity index of 858, superior even to established antitrypanosomal drugs. We suggest that the inhibition of trypanothione reductase, which is only found in trypanosomes, might explain the observed selectivity. The high selectivity together with a cytotoxic concentration in the range of the bioavailability makes panaxynol and other polyacetylenes in general very promising lead compounds for the treatment of African trypanosomiasis. Copyright © 2012 John Wiley & Sons, Ltd.